IMPLEMENTASI KEBIJAKAN RETRIBUSI JASA UMUM (Studi Kasus Implementasi Kebijakan Parkir Di Tepi Jalan Umum Kota Palu) - Donso, Shearly (Katalogis, 2016)
The purpose of research, to find out how the implementation of policies public street front parking charges in the city of Palu and factors affecting the implementation of the policy. This study analyzed four factors that affect the implementation of policies according to the theory of George C. Edward III, namely; Communication, resources, disposition and bureaucratic structure. The method used is descriptive qualitative, informants numbering five people chosen by purposive sampling. Technique data collecting by interview, observation and documentation. The results showed all four factors analyzed, 1) Communication and socialization in the bureaucratic environment quite well, the communication at the level of the structure of governance mechanisms Pakir especially with the Office of Technical Implementation Unit coordinator is not running optimally. 2) The resources in the form of means of transportation, lack of budget affects the implementation of supervision. 3) Disposition implementing agency needs to coaching, so the application of the target to the parking attendants per day will positively correlated with revenue. 4) The bureaucratic structure Perparkiran Office Technical Implementation Unit has been good, but the structure of governance mechanisms are put parking non-bureaucratic apparatus at the coordinator level ineffective. Supporting factors ; The trust of the public is still quite good and inhibiting factors Fragmentation.